CONSIDERATIONS REGARDING THE GENERAL ASPECTS OF THE SUCCESSIONAL OPTION IN THE LIGHT OF THE NEW CIVIL CODE - ILIOARA GENOIU (Challenges of the Knowledge Society)
Law no. 287/2009 regarding the Civil Code, whose date of entry in force has not been established yet, brings in the successional option matter many new elements, reconfiguring it in some parts. In this paper we will analyze the general aspects of the successional option in the light of the new Civil Code dispositions. We will thus be able to reveal the novelties brought by the new regulation in the matter subjected to our analysis and to appreciate its progressive nature. As regards the general aspects of the successional option, the new Civil Code innovates mainly relative to the term of successional option. We hope that through our approach, we enrol in the overall effort to make known and understood the disposition of the new Civil Code, until its entry in force.